Sunteți pe pagina 1din 23

EE480.

3 Digital Control Systems

Part 2. z-transform

Kunio Takaya
Electrical and Computer Engineering

University of Saskatchewan

January 14, 2008

** Go to full-screen mode now by hitting CTRL-L

1
Contents

1 z-Transform 3

2 z-transform of simple functions 3

3 Properties of the z-transform 8

4 Continue to discrete time systems 23

2
1 z-Transform

The definition of the z-Transform is


+
X
X(z) = x(k)z k .
k=

where, x(k) is a discrete time sequence (sampled data). When x(k)


is defined for k 0, i.e. causal, one sided z-transform is given by
+
X
X(z) = x(k)z k .
k=0

The variable z is complex, so is X(z).

3
2 z-transform of simple functions

function
1 if k = 0
(k) =
0 otherwise
+
X
Z[(k)] = (k)z k = 1
k=0
unit step function

1 if k 0
u(k) =
0 if k < 0

+
X
Z[u(k)] = u(k)z k = z 0 + z 1 + z 2 + +z 3
k=0

4
Since the sum of n terms of a geometric progression is given by the
formula,
n1
X
k 1 rn
ar = a
1r
k=0

1 z n 1
Z[u(k)] = lim = .
n 1 z 1 1z 1

This z-trnasform is valid only for jzj < 1, in the region of


convergence in the z-plane.

Decaying exponential function

f (t) = eat t 0, sampled with a sampling period T

f (k) = eaT k , k 0

5

X
X
Z[f (k)] = eaT k z k = (eaT z 1 )k
k=0 k=0
1
=
1 eaT z 1
The region of convergence is eaT < jzj. If a > 0, the system is
stable and the pole at z = eaT < 1 is inside the unit circle. If
a < 0, the system is unstable and the pole at z = eaT > 1 is
outside the unit circle.

Damped cosine wave

f (k) = eaT k cos T k, k 0


X
Z[f (k)] = eaT k cos T k z k
k=0

6

1 X aT +jT 1 k 1 X aT jT 1 k
= (e z ) + (e z )
2 2
k=0 k=0
1 1 1 1
= +
2 1 eaT +jT z 1 2 1 eaT jT z 1
1 eaT cos T z 1
=
1 2eaT cos T z 1 + e2aT z 2
z 2 eaT cos T z
=
z 2 2eaT cos T z + e2aT
The region of convergence is eaT < jzj.

Exercise: Find the z-transform of a discrete sequence

f (k) = 2k for k 0

7
3 Properties of the z-transform

Shift Operations - One step delay with u(k)



X
Z[x(k 1)u(k)] = x(k 1)z k
k=0

X
= x(k)z (k+1)
k=1

X
= x(k)z k1 + x(1)z 0
k=0

X
= z 1 x(k)z k + x(1)
k=0

= z 1 Z[x(k)u(k)] + x(1)

8
Shift Operations - One step delay with u(k 1)

X
Z[x(k 1)u(k 1)] = x(k 1)z k
k=1
X
= x(k)z (k+1)
k=0

X
= z 1 x(k)z k
k=0

= z 1 Z[x(k)u(k)]

Shift Operations - m step delay with u(k)



X
Z[x(k m)u(k)] = x(k m)z k
k=0

9

X
= x(k)z (k+m)
k=m

X 1
X
= x(k)z km + x(k)z km
k=0 k=m

X m
X
= z m x(k)z k + x(k)z km
k=0 k=1
Xm
= z m Z[x(k)u(k)] + x(k)z km
k=1

Shift Operations - m step delay with u(k m)



X
Z[x(k m)u(k m)] = x(k m)z k
k=m
X
= x(k)z (k+m)
k=0

10
= z m Z[x(k)u(k)]

Shift Operations - m step time advance with u(k + m)



X
Z[x(k + m)u(k + m)] = x(k + m)z k
k=m
X
= x(k)z (km)
k=0
+m
= z Z[x(k)u(k)]

Initial Value theorem


+
X
lim X(z) = lim x(k)z k = x(0)
z z
k=0

Final Value theorem

Z[x(k + 1)u(k)] Z[x(k)u(k)]

11
= zX(z) zx(0) X(z)
X
X
= x(k + 1)z k x(k)z k
k=0 k=0

X
X
zX(z) X(z) = zx(0) + x(k + 1)z k x(k)z k
k=0 k=0

X
X
lim (z 1)X(z) = x(0) + x(k + 1) x(k)
z1
k=0 k=0
= x()

Derivative

dX(z) d X
= x(k)z k
dz dz
k=0

X d k
= x(k) z
dz
k=0

12

X
= x(k)kz k1
k=0
1
= z Z[kx(k)]
dX(z)
Z[kx(k)] = z
dz
Example:
d 1
Z[ku(k)] = z
dz 1 z 1
z 2
= z
(1 z 1 )2
z 1 z
= =
(1 z 1 )2 (z 1)2

Convolution

13
Consider multiplying G(z) and X(z).

G(z)X(z)

X
X
= g(k)z k x(k)z k
k=0 k=0
1
= [g(0) + g(1)z + g(2)z 2 + g(3)z 3 + ]
[x(0) + x(1)z 1 + x(2)z 2 + x(3)z 3 + ]
= g(0)x(0) + [g(0)x(1) + g(1)x(0)]z 1
+ [g(0)x(2) + g(1)x(1) + g(2)x(0)]z 2
+ [g(0)x(3) + g(1)x(2) + g(2)x(1) + g(32)x(0)]z 3
Xn
+ g(k)x(n k) z n +
k=0
X Xn
= g(k)x(n k) z n
n=0 k=0

14
n
X n
X
= Z[ g(k)x(n k)] = Z[ x(k)g(n k)]
k=0 k=0

Input Sequence Impulse Response Output Sequence

X(z) G(z) Y(z)=G(z)X(z)

Figure: Convolution and Transfer Function

When an input sequence x(k) is applied to a system having an


impulse response g(k), the response y(k) of the system is given the
convolution sum.
Xk
y(k) = x(n)g(k n)
n=0

The equivalent expression in the z-transform is Y (z) = G(z)X(z).

15
Inverse z-Transform

Partial Fraction Method


The z-transform of an exponential sequence x(k) = ak is given by
1 z
X(z) = 1
= .
1 az za
Any sequence that starts with a non-zero value at k = 0 usually
has the same order in the numerator and denominator of the
z-transform. To find the inverse z-transform, one must take partial
X(z)
fraction expansion on instead of X(z) itself.
z
0 X(z) B(z)
X (z) = =
z (z a1 )k (z a2 )(z a3 )
c11 c12 c1k
= + + +
(z a1 )k (z a1 )k1 (z a1 )

16
c2 c3
+ + +
(z a2 ) (z a3 )
Where, unknown coefficients are given by

ci = (z ai ) X 0 (z)jz=ai
n1

1 d k 0

c1n = n1
(z a1 ) X (z)
(n 1)! dz z=a1

After partial fraction expansion, find the expanded form of X(z) by


multiplying X 0 (z) by z, then find the inverse z-transform
term-by-term by table look-up.
Example

1
E(z) =
(z 1)(z 2)
E(z) 11 1 1 1
= +
z 2z z1 2z2

17
1 z 1 z
E(z) = +
2 z1 2z2
1 1
e(k) = ( (k) 1k + 2k )u(k)
2 2

Exercise: Find the inverse z-transform of


1
Y (z) =
(1 z 1 )(1 2z 1 )

Use of MATLAB for partial fraction expansion


>> [r,p,k]=residue([1],[1, -3, 2, 0])

r =
0.5000
-1.0000
0.5000
p =
2
1

18
0
k =
[]

Difference Equation

y(k) + a1 y(k 1) + a2 y(k 2) + + ak y(0)


= b0 u(k) + b1 u(k 1) + + bk u(0)

Where, y(k) is output sequence, and u(k) is input sequence. In


control systems, b0 is often 0, as input u(k) does not immediately
affect output y(k). Take the z-transform of this difference equation
considering u(k) = 0 and y(k) = 0 for k < 0.

Z f[y(k) + a1 y(k 1) + a2 y(k 2) + + ak y(0)]u(k)g

= Z f[b0 u(k) + b1 u(k 1) + + bk u(0))]u(k)g

19
Since Z[y(k i)] = z i Y (z) and Z[u(k i)] = z i U (z),

Y (z) + a1 z 1 Y (z) + a2 z 2 Y (z) + + ak z k Y (z)

= b0 U (z) + b1 z 1 U (z) + b2 z 2 U (z) + + bk z k U (z)


This leads to a transfer function of the difference equation.
Y (z) b0 + b1 z 1 + b2 z 2 + + bk z k
G(z) = =
U (z) 1 + a1 z 1 + a2 z 2 + + ak z k
The output Y (z) for a given input U (z) is given by
b0 + b1 z 1 + b2 z 2 + + bk z k
Y (z) = G(z)U (z) = 1 2 k
U (z)
1 + a1 z + a2 z + + ak z
Example

A difference equation,

m(k) = e(k) e(k 1) m(k 1)

20
is driven by an input sequence

1, k 0 even
e(k) =
0, k 0 odd

Using the z-Transform,


z1
M (z) = E(z)
z+1
1 z2
E(z) = = 2
1 z 2 z 1
Thus, the solution in the z-Transform is
z2 z2
M (z) = =
z 2 + 2z + 1 (z + 1)2
= 1 2z 1 + 3z 2 4z 3 +

21
Assignment No. 2

Solve following problems related to the z-transform fundamentals


in the textbook pp. 78-79.

1. 2-1

2. 2-2 (a)(b)

3. 2-3 (c)

4. 2-4

5. 2-8 (a)(e) Do only the partial fraction expansion method.

22
4 Continue to discrete time systems

23

S-ar putea să vă placă și